Acute cellular rejection with isolated v‐lesions is not associated with more favorable outcomes than vascular rejection with more tubulointerstitial inflammations. (11th March 2014) - Wu, K. Y.; Budde, K.; Schmidt, D.; Neumayer, H. H.; Rudolph, B.
Abstract Background The impact of isolated v‐lesions on clinical outcome in biopsies with acute cellular rejection (ACR) is unclear. Methods Two hundred and sixty‐five biopsies showing the highest ACR severity for each patient were recruited and classified into four groups: (i) acute interstitial rejection (AIR) I with minimal tubulointerstitial inflammation (TI), (ii) AIR II with intensive TI, (iii) acute vascular rejection (AVR) I with minimal TI, and (iv) AVR II with intensive TI. Results The complete reversal rates of AIR I and AIR II groups were marginally higher than AVR I and AVR II groups (p = 0.16). At eight yr of transplantation, the death‐censored graft survival (DCGS) rate of AIR I group (93.3%) was significantly higher compared with the AVR I (72.7%) or AVR II (72.9%) group. AVR I group had a similar DCGS rate with AVR II group (72.7% vs. 74.1%), whereas AVR with v1‐lesion showed significantly higher graft survival (GS) rate than those with v2‐lesion (70.2% vs. 45.5%). The t‐lesion of AIR and v‐lesion of AVR group were associated with graft loss. Conclusion The extent of TI is non‐specifically associated with graft loss in biopsies with AVR; the higher grade v‐lesion predicts the lower complete reversal rate and poorer long‐term graft survival.